HUBUNGAN HIPERTENSI DALAM KEHAMILAN DENGAN KEJADIAN IUGR DI RSUD PANEMBAHAN SENOPATI BANTUL - Septiani, Dessy Nur; Santoso, Sabar; Sujiyatini, Sujiyatini (Jurnal Kesehatan Ibu dan Anak, 2013)
Neonatal mortality rate in Province of Special region Yogyakarta on 2012 are 241 case or 5,5 per 1000 live births, with the most death caused by low birth weight. LBW divided to 2 categories, are LBW caused by premature and by IUGR. the highest IUGR incident in Province Yogyakarta was at Bantul District 14%. One of the factors which caused IUGR is hypertension gravidarum. Purpose: to identify correlation of hypertension gravidarum with intrauterine Growth Restriction (IUGR) incident in Panembahan Senopati General Hospital 2011. Method: this study is a non-experiment by analytic observational with case control study, with 40 with IUGR as case group and 40 with average weight for control group. Technik sampling used purposive sampling. instrument of study is roundup data format used secondary data. Analysis data used bivariate using chi-square. Result: there are 65% babies who born with IUGR in woman with hypertension gravidarum, and 34% ones in women normal blood pressure. The result chi square test is p-value 0,00< 0,05 and Odd ratio 3,449. Conclusion; this study showed there is a significant correlation of hypertension gravidarum with IUGR incident, from odd ratio there is pregnant women with hypertension increased risk of IUGR incident.